DETERMINATION OF OPERATING STRESS IN SHOVEL BOOM AT RECLAMATION WORK - Valery E. Kasyanov; Marina M. Zaytseva; Anastasia A. Kotesova; Anatoly A. Kotesov (Advanced Engineering Research, 2011)
The method of determining Fisher—Tippett distribution parameters of final volume parent population (Ас, Вс, Сс) under the sampled data of the average stress is offered. Thereby, average values of Ас, Вс, Сс parametres obtained in the repetitive simulation are recommended to use.